Bigger fish to fry: Should the reform of cross-examination be expanded beyond vulnerable witnesses?. (April 2015) - Henderson, Emily
The author summarises the empirical research on robust adult witnesses and argues that consideration may need to be given to extending the reforms of cross-examination initiated in R v Barker beyond vulnerable witnesses.